Gerenciamento de processos industriais baseado em princípios da produção mais limpa - Bohm, Sandra Inês Horn (2011)
Cleaner production (CP) is the continuous application of a preventive environmental strategy process associated to the products and services of an organization, with the goal of increasing efficiency and reducing risks to human beings and the environment. Its implementation has generally increased productivity from the rational use of resources. Total Performance Scorecard (TPS) is a sistematic learning process, developing and continuous improvement, based on the sustainable growth of personal and corporate actions. The objective of this research was to propose a strategy to manage organizational processes, based on the principles of cleaner production in metal mechanic companies. The proposal for maintenance and continuity of improvements is based on the TPS cycle. The research was made from the data of a producer of agricultural machines in Rio Grande do Sul, which has the objective of reducing scrap in its processes. Three cases were considered in this research: obsoletes items, purchasing process of sheet metals and cutting the sheet metals to produce the pieces. The data show a significant improvement with the use of the cleaner production principles in the researched processes.